Programmed death (PD)-1:PD-ligand 1/PD-ligand 2 pathway inhibits T cell effector functions during human tuberculosis - Jurado, Javier Oscar (2008)
Protective immunity against Mycobacterium tuberculosis requires the generation of cell-mediated immunity. We investigated the expression and role of programmed death 1 (PD-1) and its ligands, molecules known to modulate T cell activation, in the regulation of IFN-γ production and lytic degranulation during human tuberculosis. We demonstrated that specific Ag-stimulation increased CD3+PD-1+ lymphocytes in peripheral blood and pleural fluid from tuberculosis patients in direct correlation with IFN-γ production from these individuals. Moreover, M. tuberculosis-induced IFN-γ participated in the up-regulation of PD-1 expression. Blockage of PD-1 or PD-1 and its ligands (PD-Ls: PD-L1, PD-L2) enhanced the specific degranulation of CD8+ T cells and the percentage, of specific IFN-γ-producing lymphocytes against the pathogen, demonstrating that the PD-1:PD-Ls pathway inhibits T cell effector functions during active M. tuberculosis infection. Furthermore, the simultaneous blockage of the inhibitory receptor PD-1 together with the activation of the costimulatory protein signaling lymphocytic activation molecule led to the promotion of protective IFN-γ responses to M. tuberculosis, even in patients with weak cell-mediated immunity against the bacteria. Together, we demonstrated that PD-1 interferes with T cell effector functions against M. tuberculosis, suggesting that PD-1 has a key regulatory role during the immune response of the host to the pathogen.